Dental bleaching effects on periodontal tissues. Literature review - Aldana-Sepúlveda, Heberth; Vivas-Moncayo, Juan-Carlos (Revista Estomatología, 2016)
Several clinical studies have evaluated the effectiveness of short and long term bleaches hydrogen peroxide (H2O2 ) agents, also its adverse effects on hard and soft tissues, finding that tooth and gingival sensitivity are the most frequent. However, these studies only based on clinical observations and perceptions of patients. The purpose of this review is to describe, based on scientific evidence in vitro and in vivo, the major side effects generated by H2O2 on periodontal tissues and cell populations, providing clinical relevance’s to provide clinicians useful advice when selecting and establishing protocols to patients seeking this type of treatment, aiming at reducing injuries to periodontal tissue support. We conclude that the use of these chemicals, but still generate immediate undesirable effects such as tooth sensitivity and gingival irritation, and based on the dose exposure time relationship, it’s a safe treatment. However, we should not underestimate the potential harmful effects that can produce their abuse or misuse, hence the importance of knowing their chemical composition and effects on structures that apply, and always from a dental and periodontal health for application.